2022
DOI: 10.1093/ijnp/pyac002
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Discontinuation of Antipsychotics in Patients Who Recover From First-Episode Schizophrenia Spectrum Disorders: Derived From the Aggregated Opinions of Asian Network of Early Psychosis Experts and Literature Review

Abstract: Objective Antipsychotic discontinuation has been a long-standing clinical and medicolegal issue. The Asian Network of Early Psychosis developed guidelines for antipsychotic discontinuation in patients who recover from first-episode non-affective psychosis. We reviewed the existing studies and guidelines on antipsychotic discontinuation, to develop guidelines for antipsychotic discontinuation in such patients. Methods We revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 88 publications
(132 reference statements)
0
5
0
Order By: Relevance
“…Statistical heterogeneity was explored using subgroup analysis. Subgroup analyses were done to explore the effect of risk of bias (high, some concerns, and low risk), types of antipsychotics (first-generation, second-generation, or mixed), use of injectable antipsychotics (oral, long-acting injectable, mixed), mean antipsychotics defined daily doses (DDD) used (low [<0.9 DDD], normal [≥0.9 and <1.1 DDD] and high [≥1.1 DDD]), sex (female, male, or mixed), discontinuation methods (abrupt and gradual discontinuation), and remission duration (short [≤12 months], medium [>12 months and ≤18 months], and long duration [>18 months]) [ 3 , 26 , 27 ]. The selection of these subgroup analyses was informed by the understanding that the characteristics of antipsychotics, study quality, duration of remission, and discontinuation strategies may influence recovery outcomes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Statistical heterogeneity was explored using subgroup analysis. Subgroup analyses were done to explore the effect of risk of bias (high, some concerns, and low risk), types of antipsychotics (first-generation, second-generation, or mixed), use of injectable antipsychotics (oral, long-acting injectable, mixed), mean antipsychotics defined daily doses (DDD) used (low [<0.9 DDD], normal [≥0.9 and <1.1 DDD] and high [≥1.1 DDD]), sex (female, male, or mixed), discontinuation methods (abrupt and gradual discontinuation), and remission duration (short [≤12 months], medium [>12 months and ≤18 months], and long duration [>18 months]) [ 3 , 26 , 27 ]. The selection of these subgroup analyses was informed by the understanding that the characteristics of antipsychotics, study quality, duration of remission, and discontinuation strategies may influence recovery outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…Antipsychotics have proven efficacy in treating first-episode psychosis (FEP) as they allow achieving a rate of symptomatic remission at 12 months of approximately 54% [ 1 ]. However, uncertainty persists regarding the optimal duration of treatment beyond the initial episode, guidelines recommending treatment maintenance for periods of at least 1–5 years, depending on the guidelines considered [ 2 , 3 ]. Two meta-analyses of randomized controlled trials (RCTs) published in 2018 found a higher rate of psychotic relapse in patients discontinuing treatment [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For individuals who achieved both symptomatic and functional recovery, there is a need to determine when and how antipsychotic medication should be discontinued. We recently published “Guidelines for discontinuation of antipsychotics in patients who recover from first-episode schizophrenia spectrum disorders” [ 5 , 6 ]. In the guidelines, we suggested using stricter criteria when deciding whether to discontinue antipsychotics, rather than Andreasen’s criteria (which are most frequently used in discontinuation trials) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…They showed altered functional connectivity (FC) [ 11 ], as well as changes in the activities of specific brain regions, while the patients performed tasks [ 10 , 12 ]. However, the participants in those studies did not meet our strict criteria for full recovery [ 3 , 5 ]. SZ has been explained in terms of aberrant interactions among brain regions, leading to the degeneration of brain networks; this degeneration is referred to as disconnection syndrome [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%